Lembar Kerja Genetika yang Inovatif Bagi Guru IPA - Suci Siti Latifah; Lilis Supratman; Aip M. Irpan; Azzura Gryniprillady Meyradhia; Angel Aulia Haritsa (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity aims to create contextually-oriented learning and teaching materials for Grade 9 students on the topic of inheritance. The purpose of this activity is to support MGMP teachers in Bogor district. The teaching methods employed during this training activity include lectures, discussions, guidance and hands-on instruction, as well as virtual consultation sessions through Zoom meetings and WhatsApp groups. Lectures and discussions were utilized to present objective information on the concept of crosses, including real-world examples and innovative applications for creating case study-based LKPD. Guidance and training methods, including Zoom meetings and online groups, were employed to finalize and improve knowledge transfer from lectures and discussions. Design abilities of innovative LKPD concepts were improved through training and mentoring on the concept of crossover. The average score before the training was 43, while the posttest score increased to 73. Based on the success indicators of implementing PkM activities for the development of innovative worksheet learning, it was discovered that all participants achieved success in designing LKPD based on case studies. The efficacy of training activities can be gauged by evaluating participant feedback on the usefulness of said activities, grouped into four categories. The results indicate that 73% of participants found the training activities to be "very useful," while the remaining 27% found them "useful."